Playboys and killjoys : an essay on the theory and practice of comedy - Levin, Harry, 1912-1994 (Oxford University Press, 1988)
Harry Levin--one of America's leading literary critics--offers a study of the whole world of comedy, concentrating on playwrights through the centuries, from Aristophanes and Plautus in classical times to Bernard Shaw and Bertolt Brecht and their recent successors.